Diphtheria outbreak triggered by low vaccine coverage and socioeconomic status in 2023: Nigeria - Kama, John; Sanusi Karama, Rahama; Prithvi, Jalamanchili (International Journal Of Community Medicine And Public Health, 2024)
Diphtheria is a highly contagious bacterial infection that primarily affects the throat and upper airways. Before the introduction of vaccines, there were many cases and fatalities from diphtheria. During the 1920s, over 150,000 cases of diphtheria with an average of 14,000 deaths reported each year in the United States of America. Ever since the diphtheria toxoid vaccine has been made available in the 1940s, there have been a massive decline in diphtheria morbidities and mortalities in developed countries as compared to developing and underdeveloped countries. The socioeconomic status of Nigeria could have contributed to the recent Outbreak of diphtheria. As a country, Nigeria has struggled to have a functioning Economy system but still no solution despite efforts from the government. For instance, the recent outbreak has been linked to low vaccine coverage especially in rural communities in the country. Poor access to healthcare has also played a role on the basis of insecurity and inadequate functioning health infrastructures. There is little or no awareness, conferences, workshops concerning the importance of vaccination all because of shortage of health workers in the country. Most of these factors above, have leads us to experiencing symptoms of diphtheria such as sore throat, low-grade fever, weakness, and difficulty breathing recently. Diphtheria can be prevented if vaccination is done as scheduled by the WHO (World Health Organization) and NPI (National programme for immunization). To prevent future outbreaks, low vaccine coverage and socioeconomic status must be tackled effectively by the Nigerian Government.